2022
DOI: 10.12701/jyms.2022.00311
|View full text |Cite
|
Sign up to set email alerts
|

Novel cystography parameter to predict early recovery from urinary continence after radical prostatectomy for prostate cancer: a retrospective study

Abstract: Radical prostatectomy (RP) is the definitive treatment for localized prostate cancer. However, post-prostatectomy incontinence (PPI) is a significant surgical complication after RP that can influence a patient's quality of life. The major causes of PPI include Background: The purpose of this study was to investigate whether postoperative cystography findings can predict early and longterm recovery from incontinence after radical prostatectomy (RP), compared with the other cystography parameters. Methods: I ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…It is difficult to conclusively decipher the underlying mechanisms behind immediate urinary continence achievement after ULP‐RARP, but one possible explanation could be a narrow vesicourethral angle. Previous reports have shown that a narrow vesicourethral angle was associated with improved urinary continence 13–17 . In this study, postoperative urethral cystography showed that the vesicourethral angle was narrower in the ULP‐RARP group than in the S‐RARP group.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…It is difficult to conclusively decipher the underlying mechanisms behind immediate urinary continence achievement after ULP‐RARP, but one possible explanation could be a narrow vesicourethral angle. Previous reports have shown that a narrow vesicourethral angle was associated with improved urinary continence 13–17 . In this study, postoperative urethral cystography showed that the vesicourethral angle was narrower in the ULP‐RARP group than in the S‐RARP group.…”
Section: Discussionsupporting
confidence: 47%
“…Previous reports have shown that a narrow vesicourethral angle was associated with improved urinary continence. [13][14][15][16][17] In this study, postoperative urethral cystography showed that the vesicourethral angle was narrower in the ULP-RARP group than in the S-RARP group. This may be a potential explanation for the positive effect of ULP-RARP on postoperative urinary continence.…”
Section: Discussionmentioning
confidence: 51%